The influence of temperament on stress‐induced emotional eating in children - Tara Kristen Ohrt; Marisol Perez; Jeffrey Liew; Juan Carlos Hernández; Kimberly Yim Yu (Wiley, 2020)
Summary Background Stress‐induced emotional eating is a risk factor for overweight and obesity. Previous research proposes both the human serotonin transporter gene (5‐HTTLPR) and child's reactive temperament are promising candidates to help explain individual differences in stress‐induced emotional eating and weight. Understanding the association between specific genotypes, reactive temperament factors, and stress‐induced emotional eating may inform the development of personalized and effective treatment for children who may be at risk for overweight and obesity. Objective The current study explored the conditional indirect effect of genetic and environmental susceptibility (i.e., the interaction between 5‐HTTLPR and reactive temperament) on weight (as measured by percent body fat) mediated by stress‐induced emotional eating. Method One hundred and forty‐seven children (4 to 6 years old; 50.3% female; 22.4% Hispanic), along with their primary caregiver, completed laboratory tasks and questionnaires that assessed the child's reactive temperament, stress‐induced emotional eating, and percent body fat. Results The interaction between 5‐HTTLPR and impulsivity as well as with negative affectivity significantly predicted percent body fat. The interaction between 5‐HTTLPR and impulsivity as well as with negative affectivity significantly predicted both total calorie consumption and rate of total calorie consumption. However, the mediation aspect of this statistical model was not supported. Conclusions Child reactive temperament is an important indicator of how children approach eating when stressed. Mental health providers may consider prescribing strategies to reduce emotional eating among children with the SL variant and moderate to high impulsivity as well as children with the LL variant and high negative affectivity.